Does peer assessment in on-line learning environments work? A systematic review of the literature. (November 2016) - Tenório, Thyago; Bittencourt, Ig Ibert; Isotani, Seiji; Silva, Alan Pedro
Abstract: There is an increase use of Peer Assessment (PA) approaches in On-line Learning Environments to support students and teachers on educational process. However, the community still lacks a comprehensive understanding of how Peer Assessment behaves within these educational environments, since there are no studies that make an analysis of the researches which has been conducted in this context, analysing the benefits and disadvantages of the use of Peer Assessment. Thus, the main goal of this work is to investigate and better understand how PA contributes in student learning as well as can bring benefits to the teachers involved. In order to meet our goal, we conducted a systematic literature review (SLR). In summary, the main findings are: (1) there are empirical evidences of the benefits of using PA in both industry and academy, and in several educational levels; (2) PA is most addressed to the correction of written activities on on-line courses; (3) About 60% of the articles showed PA improvement in student performance; (4) About 1/3 of the studies showed PA brings some benefits to teachers; (5) In some studies the use of the PA had difficulties, especially issues related to student motivation, which impairs the peer review process. Highlights: We conducted a SLR to identify the use of Peer Assessment(PA)in On-line Learning. The results show there are empirical evidences of the benefits of using PA approaches. About 60%of the studies indicates that PA improvement in student performance. About 1/3 of the studies showed that Peer Assessment brings benefits to teachers.